Evaluation Of Blood Pressure Lowering Efficacy Of Sustained Release : Indapamide Formulation Over Bangladeshi Hypertensive Patient - Habib, Maruf Bin; Afsar, Nikhat Shahla; Latif , Tanveer Bin; Ali, Md Hyder; Nizamuddin, Md (Journal of Chittagong Medical College Teachers' Association, 2013)
The use of thiazide-type-diuretic is recommended in different guidelines to treat hypertensive patients. Indapamide SR provides powerful BP control without disturbing electrolyte parameters. The aim of this study was to evaluate Indapamide SR for Bangladeshi hypertensive patients in terms of BP reduction efficacy as well as no adverse effect on serum electrolytes. 46 hypertensive patients with age ? 18 without any renal or hepatic disease were enrolled in the study. Indapamide SR initiated for the newly diagnosed hypertensive patients (46%) and in some cases added (54%), where they were uncontrolled on previous antihypertensive medications. Six months later their BP reduction was evaluated by taking the average of three consecutive clinic BP recordings during the visit. At the same time their serum sodium and potassium level was compared with the standard range. The analysis was carried out on all patients, both new & previously uncontrolled patients. The previously uncontrolled group was also further evaluated. The overall BP reduction with Indapamide SR after 6 months was -21.9 /-17.7 mmHg from the average baseline BP (p< 0.0001). SD for final SBP and DBP average was +11 and +6 mmHg respectively. The average sodium and potassium level at serum was found to be 139.04 = 2.79 mEq/L and 3.93 € 0.31mEq/L respectively which was within the normal range. In the subgroup analysis, BP reduction was as follows- New patients: -21.8/17.7 mmHg; Previously Uncontrolled patients: - 22.1/17.7 mmHg; Uncontrolled on monotherapy: - 25.7/17.1 mmHg & Uncontrolled on Combination therapy: -16.3/18.8 mmHg. The electrolyte parameter among all the subgroup was found to be within the standard range. This observational study suggest that Indapamide SR provides powerful BP reductions both in new and uncontrolled patients without disturbing serum sodium and potassium level. Matching other evidences and guideline recommendations, we may consider Indapamide SR as a choice of drug in our clinical practice. JCMCTA 2013 ; 24 (1): 22-27